Consumer Preference for Food Bundles under Cognitive Load: A Grocery Shopping Experiment - Kathryn A. Carroll; Anya Samek; Lydia Zepeda (Foods, 2022)
Product bundling is a common retail marketing strategy. The bundling of food items has the potential to increase profits in the grocery sector, particularly for fresh produce, which often has lower profit margins. Although prior work suggests consumers prefer bundles because they require less cognitive effort to select, no study has yet experimentally manipulated cognitive load when food bundles are included in the choice set. To test whether bundle preference differs when cognitive resources are constrained, a grocery shopping experiment was conducted with 250 consumers in the midwestern U.S., in a laboratory that featured a grocery store display. Consumers who grocery shopped under cognitive load had a higher odds of selecting a food bundle even when the bundle did not offer a price discount. Results suggest food bundles may be preferred because they require less cognitive effort to process, which could benefit consumers by simplifying the grocery shopping experience. Additional factors found to influence food bundle selection included whether the bundled items were perceived as being complementary and hunger levels. Food bundles could help lessen cognitive effort associated with grocery shopping and may especially appeal to those who do not enjoy food shopping.